2007
DOI: 10.1111/j.1540-8159.2007.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor Prognosis for Patients with Chronic Kidney Disease Despite ICD Therapy for the Primary Prevention of Sudden Death

Abstract: In patients receiving an ICD for primary prevention of sudden death, CKD significantly reduced long-term survival. This poor prognosis may limit the impact of primary prevention ICD therapy in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 39 publications
3
86
1
Order By: Relevance
“…Investigators have reported that patients with advanced age and chronic renal failure do not benefit from primary prevention ICDs because of imminent, competing causes of death. [12][13][14] Both the risk-benefit and cost-benefit ratios of primary prevention ICD therapy would be improved by strategies to exclude presently indicated patients who are unlikely to benefit, if they could be identified accurately.…”
Section: Article See P 835mentioning
confidence: 99%
“…Investigators have reported that patients with advanced age and chronic renal failure do not benefit from primary prevention ICDs because of imminent, competing causes of death. [12][13][14] Both the risk-benefit and cost-benefit ratios of primary prevention ICD therapy would be improved by strategies to exclude presently indicated patients who are unlikely to benefit, if they could be identified accurately.…”
Section: Article See P 835mentioning
confidence: 99%
“…16 In a retrospective study of 35 patients with chronic kidney disease, out of 229 who had an ICD implanted for primary prevention, Cuculich et al registered a one-year survival of 61.8% in patients with a serum creatinine of >177 µmol/l or on chronic dialysis, compared with 96.3% in controls. 17 This lack of benefit in the more diseased population was also apparent in the SCDHeFT trial: whereas in NYHA class II patients there was a 46% reduction in risk of death, patients in NYHA class III had no advantage with an ICD compared with placebo.…”
Section: Limitations Of Current Guidelinesmentioning
confidence: 96%
“…An increasing number of noncardiac comorbidities has the potential to blunt or negate the benefit of ICD therapy due to competing risks for death [52]. The potential futility of ICD efficacy in patients with chronic and end-stage renal disease has been suggested by multiple retrospective cohort analyses [70][71][72][73]. The Charlson comorbidity index (CCI) is widely used as an adjustment variable in prognostic models [74].…”
Section: Comorbiditymentioning
confidence: 99%